Dog heroes : a story poster book with tales of dramatic rescues, courageous journeys, and true-blue friendships - Meyer, Karl. (North Adams, MA : Storey Pub., 2008)
Collects stories and full-color photographs of dogs who have performed heroic actions to save the lives of humans, and describes dogs that have rescued drowning sailors, saved a family from a fire, and more.
Includes bibliographical references.
5.1
3-6
Keywords: Search dogs -- Juvenile literature; Rescue dogs -- Juvenile literature; Search dogs; Rescue dogs; Search dogs; Rescue dogs